Inhibitors of mutant isocitrate dehydrogenases 1 and 2 (mIDH1/2): an update and perspective - Ma, Tianfang; Zou, Fangxia; Pusch, Stefan; Xu, Yungen; Deimling, Andreas von; Zha, Xiaoming (Journal of medicinal chemistry, 2018)
Isocitrate dehydrogenases 1 and 2 (IDH1/2) are homodimeric enzymes that catalyze the conversion of isocitrate to α-ketoglutarate (α-KG) in the tricarboxylic acid cycle. However, mutant IDH1/2 (mIDH1/2) reduces α-KG to the oncometabolite 2-hydroxyglutarate (2-HG). High levels of 2-HG competitively inhibit the α-KG-dependent dioxygenases involved in histone and DNA demethylation, thereby impairing normal cellular differentiation and promoting tumor development. Thus, small molecules that inhibit these mutant enzymes may be therapeutically beneficial. Recently, an increasing number of mIDH1/2 inhibitors have been reported. In this review, we summarize the molecular basis of mIDH1/2 and the activity, binding modes, and progress in clinical application of mIDH1/2 inhibitors. We note important future research directions for mIDH1/2 inhibitors and discuss potential therapeutic strategies for the development of mIDH1/2 inhibitors to treat IDH1/2 mutated tumors.